Transition in Adolescents: a Study on Changes in Social Cohesion - C. Jaison, M; Prathiba, N; Ranjit, L (International Journal of Engineering and Technology, 2018)
Human growth begins with conception and developed through different unique stages and ends with death. Each stage has its own characteristics. Adolescent period is also one of such unique period in Human Growth. Even though there are development in physical health of adolescent during these decades mental health of adolescent is not marked such evidential growth in overall mental health. Since Adolescent period is the important and crucial period of moulding mental health. Department of Health, Republic of South Africa in 2001 mentioned four dimensions of adolescent mental health. They are mental, emotional, social and spiritual. The study primarily focuses on the social dimension of adolescent mental health.Â Â